Multi-applicative tetragonal TiO2/SnO2 nanocomposites for photocatalysis and gas sensing. (April 2018) - Patil, S.M.; Dhodamani, A.G.; Vanalakar, S.A.; Deshmukh, S.P.; Delekar, S.D.
Abstract: TiO2 -based mixed metal oxide heteronanostructures have multiple applications in photocatalysis and gas sensing because of their charge transport properties. In this study, we prepared tetragonal TiO2 /SnO2 nanocomposites (NCs) with different weight percentages using a simple wet impregnation method. The physicochemical properties of the NCs were investigated using X-ray diffraction, Fourier transform-infrared spectroscopy, ultraviolet–visible spectroscopy, field-emission scanning electron microscopy, energy dispersive X-ray spectroscopy, transmission electron microscopy, and Brunauer–Emmett–Teller surface area analysis. The results showed that the surface area of the NCs increased significantly and the anatase TiO2 was sensitized after the addition of a small amount of cassiterite SnO2 NPs. We systematically studied the as-prepared NCs during the photocatalytic degradation of Congo Red dye under visible light irradiation (λ > 420 nm) and NH3 gas sensing, which demonstrated the efficient photocatalytic performance and the superior sensing response of the catalyst with a weight composition of 25% SnO2 in TiO2 (4:1) compared with the other NCs or the bare individual nanoparticles. The improved photocatalytic and gas sensing performance of the TiO2 /SnO2 (4:1) NCs may be attributed to the increased active surface area, the increased adsorption of the dye and target gas molecules, as well as efficient electron–hole charge separation and transfer. Highlights: Homophase (tetragonal) TiO2 /SnO2 nanocomposites (NCs) prepared by sol–gel method. Tetragonal TiO2 /SnO2 NCs visible-active photocatalysts that degraded Congo red dye. Tetragonal TiO2 /SnO2 NCs excellent NH3 gas sensors with good response/recovery.